ECONOMIC RISKS OF THE FOOD INDUSTRY OF UKRAINE IN THE CONDITIONS OF GLOBAL CHALLENGES (Development Service Industry Management, 2024)
The food industry is one of the most important sectors of the Ukrainian economy, ensuring food security, job creation, and a significant share of foreign exchange earnings from exports. However, in the current global challenges, the industry faces numerous risks that affect its sustainability and competitiveness. This article comprehensively analyzes the key economic risks of Ukraine's food industry caused by internal and external factors that determine its development. One of the biggest threats is the impact of climate change, which causes abnormal weather phenomena, particularly droughts, floods, and temperature fluctuations, which directly affect crop yield- the food industry's primary raw materials. This, in turn, leads to the instability of raw material supplies and an increase in the production costs of enterprises. Another important challenge is geopolitical instability, particularly military actions on the territory of Ukraine, which destroy production facilities, complicate logistics, and cause the loss of access to traditional export markets due to the blockade of ports and the introduction of trade restrictions. The energy crisis, manifested in the increase in the cost of energy, irregularity of their supply, and dependence on imports, also significantly affects the industry. The increase in production costs due to high energy prices reduces the competitiveness of products in both domestic and foreign markets. In addition, the COVID-19 pandemic has created additional risks, particularly due to supply chain disruptions, a decrease in the population's purchasing power, and restrictions on the functioning of enterprises, which have mainly negatively affected small and medium-sized enterprises. Another critically important factor is the dependence of the Ukrainian food industry on foreign markets since a significant part of the products are exported. This makes the industry vulnerable to fluctuations in world markets, changes in demand and supply, currency risks, and international competition. Such dependence complicates long-term planning and reduces the industry's resilience to global economic changes. The article proposes several measures to minimize these risks and ensure sustainable development of the industry. Among them, a special place is occupied by the diversification of sales markets, which will reduce dependence on traditional markets and expand the geography of exports, particularly to the markets of Asia, Africa, and Latin America.
Keywords: economic risks; food industry of Ukraine; global challenges; climate change; energy crisis; geopolitical instability; COVID-19 pandemic; market diversification; state support; competitiveness; export potential; food security